2013
DOI: 10.1159/000353137
|View full text |Cite
|
Sign up to set email alerts
|

Screening for<b><i> Cronobacter</i></b> Species in Powdered and Reconstituted Infant Formulas and from Equipment Used in Formula Preparation in Maternity Hospitals

Abstract: Background/Aims:Cronobacter spp. have been identified as being of considerable risk to neonates. The occurrence of organisms in infant formulas is therefore of considerable interest. Methods: The occurrence of Cronobacter spp. in infant feeds (formulas and fortified cow's milk) was determined using most probable number (MPN) analysis, and from formula preparation utensils. Ninety-nine samples were analyzed, of which 42 were unopened cans of powdered infant formula (PIF), 25 reconstituted infant formulas in fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…This is within the range of values found in previous studies, but not identical ( 26 , 35 – 37 ). If we consider that the pathogen has been quantified in PIF with contamination levels of 0.22–1.61 MPN/100g ( 39 ), 0.23–1.91 MPN/100g ( 40 ), and 0.023–2.3 MPN/g ( 41 ), the possibility of illness associated with consumption at these contamination levels is very real. The heterogeneous distribution of Cronobacter contamination in PIF should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This is within the range of values found in previous studies, but not identical ( 26 , 35 – 37 ). If we consider that the pathogen has been quantified in PIF with contamination levels of 0.22–1.61 MPN/100g ( 39 ), 0.23–1.91 MPN/100g ( 40 ), and 0.023–2.3 MPN/g ( 41 ), the possibility of illness associated with consumption at these contamination levels is very real. The heterogeneous distribution of Cronobacter contamination in PIF should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 described the application of MLST, which includes an initial genomic DNA extraction, PCR amplification of target genes, DNA purification of amplified fragments, Sanger sequencing, alignments to the MLST Cronobacter database, and finally MLST data outputs. This scheme has already been applied in epidemiologic investigations, screening for Cronobacter species in both commercial infant formula products and in hospital or industrial environments ( 60 , 62 , 67 , 68 ). However, Pan et al ( 62 ) reported that PFGE demonstrated a superior typing capability when compared with MLST and thereafter suggested a combined approach for the sub-typing of Cronobacter species from food and its related environments.…”
Section: Sub-typing Methodsmentioning
confidence: 99%
“…In some cases, it would not be possible to isolate Cronobacter from each parallel sample portion, and therefore we suppose that Cronobacter numbers were low as it was shown in recent study in which the Cronobacter enumeration was performed (Siqueira Santos et al . ). In three samples, multiple strains originated from parallel isolation were obtained.…”
Section: Resultsmentioning
confidence: 97%
“…It was shown recently that ST4 strains have been frequently isolated from PIFs and milk powder processing factories (Joseph and Forsythe ; Siqueira Santos et al . ; Sonbol et al . ).…”
Section: Resultsmentioning
confidence: 99%